Conversational Competencies for Corporate Governance - Avila, José Coelho; Lucena Filho, Gentil José; Figueiredo, Rejane Maria da Costa (iSys - Journal of Information Systems, 2017)
Corporate governance has been considered as a tool to realign organizations on a global context of changes in culture and values. Paradoxically, it carries historical traditions and technicist methods that are incompatible with a scenario where organizations seek to humanize their relations. How then can human and social issues be integrated with technical issues to obtain more effective results? This paper presents a study on a technical and ontological framework where leaders and managers address this integration by using conversational skills. The theories and real case study presented here show the importance of conversations for the Corporate Governance and the effectiveness of the results of organizations.